Psychology and the issue of networking in Social Assistance Policy in Brazil - Rafael Bianchi Silva; Rafaela Naomi Takahashi Osawa (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
The profession of psychologist was instituted in Brazil having as professional duties, activities related to psychological diagnosis, professional guidance and selection, psycho-pedagogical guidance and solution of self-adjustment problems. This article examines the psychologist work inside the Brazilian National Policy of Social Assistance (PNAS), regarding the issue of networking. From the network vision and its implications of working with public policies, we discuss the psychologist insertion in that policy. As objects of analysis, we use the documents that parameterize the policy of Social Assistance in Brazil and those produced by the Federal Council of Psychology (CFP), regarding to the conceptualization, importance and role of the psychologist in networking. We concluded that, from this perspective, the psychologist work implies the transversalization of practices and knowledge leading to establish new ways of doing Psychology.